Influence of an educational strategy to promote the use of regional food - Mariana Cavalcante Martins; Ádria Marcela Vieira Ferreira; Ludmila Alves do Nascimento; Julliana dos Santos Aires; Paulo César de Almeida; Lorena Barbosa Ximenes (Universidade Federal do Ceará, 2015)
Objective: to assess the knowledge, attitude and practice of family members of preschool children about regional food, through a survey before and after an educational intervention. Methods: this is a pre-experimental one-group pretest-posttest study, with 62 family members of preschool children. One month before and after the conduction of an educational activity using the flipchart "regional food promoting food security", one applied the survey. Results: it was found that after the educational strategy, there was an increase in the classification "appropriate" in each survey area about regional food, and the variation of knowledge (17.7%-77.4%), attitude (21%-72.6%) and practice (14.5%-64.5%), consequently, an improvement of 59.7% in knowledge, 51.6% in attitude and 50% in practice. Conclusion: the use of educational technology had a positive influence on the knowledge, attitudes and practice of family members, contributing thus to the health promotion of children and their family members.